QS9: Decellularization Of Vascularized Composite Allografts In The Rat. (July 2021) - LUPON, ELISE; Acun, Aylin; Goutard, Marion; Lellouch, Alexandre G.; Oganesyan, Ruben; Andrews, Alec R.; Lantieri, Laurent; Randolph, Mark A.; Cetrulo, Curtis L.; Uygun, Basak
Abstract : Purpose: The decellularization of Vascularized Composite Allotransplantation (VCA) represents a first step in circumventing the need for immunosuppression by depleting donor cells from VCAs. Here we present a model of decellularization of VCAs in rats. Methods: Rat hind limbs based upon the common femoral artery were harvested and perfused through the vascular pedicle at 1ml/min through with 1% sodium dodecyl sulfate (SDS) (group 1) or 0.2% SDS (group 2) or were immersed in SDS 1% (group 3), followed by perfusion (group 1 and 2) or immersion (group 3) in 1% Triton X-100. The degree of decellularization was assessed quantitatively by determining DNA content and qualitatively by histology in all groups at the same locations. The group yielding best decellularization outcome was selected for further assessment for the preservation of ECM content and vasculature and was transplanted orthotopically to assess the ability to reperfuse these decellularized limbs in vivo. RESULTS - Gross examination and DNA quantification of less than 50 ng/mg tissue demonstrated successful decellularization only in group 2 while preserving tissue matrix architecture, including vessels. The arterial network was found to be perfusable and intact during in vivo orthotopic transplantation of the decellularized limb. No outflow was observed, however, after 115 minutes of arterial reperfusion. Conclusions: We describe a successful decellularization protocol for rat hindlimb VCAs by perfusion ex-vivo of 1% SDS. During its in vivo transplantation, decellularization alone allows for a perfusable arterial network and with further optimization, we aim to achieve venous perfusion as well.